2020
DOI: 10.1093/asjof/ojaa050
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Differences Between Transgender Individuals With and Without History of Nonsurgical Facial Injectables

Abstract: Background A great deal of research has focused on the psychosocial characteristics of individuals who seek aesthetic procedures as well as the psychological changes they experience after successful treatment. Little research, however, has explored the experiences of transgender individuals who have undergone nonsurgical injectable procedures (NSIPs). Objectives This study examined theoretically relevant psychosocial characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…Four studies (4/13) included investigations of psychosocial outcomes of nonsurgical injectables. 14,15,20,25 Wilson et al found no significant differences in satisfaction with body appearance or feelings of passing as one's identified gender in transwomen who received filler in their lifetime (n = 33) and those who did not (n = 200), although those who received filler reported higher scores for both outcomes. However, this study was not powered to investigate the psychosocial effects of filler use, as the analyzed data originated from a survey primarily focused on assessing filler's link to HIV risk.…”
Section: Nonsurgical Injectablesmentioning
confidence: 97%
See 2 more Smart Citations
“…Four studies (4/13) included investigations of psychosocial outcomes of nonsurgical injectables. 14,15,20,25 Wilson et al found no significant differences in satisfaction with body appearance or feelings of passing as one's identified gender in transwomen who received filler in their lifetime (n = 33) and those who did not (n = 200), although those who received filler reported higher scores for both outcomes. However, this study was not powered to investigate the psychosocial effects of filler use, as the analyzed data originated from a survey primarily focused on assessing filler's link to HIV risk.…”
Section: Nonsurgical Injectablesmentioning
confidence: 97%
“…All 13 studies had their references screened however no further studies were identified for inclusion. [13][14][15][16][17][18][19][20][21][22][23][24][25] An outline of the study selection process is in Figure 1.…”
Section: Articles Retrievedmentioning
confidence: 99%
See 1 more Smart Citation
“…Les conclusions d’un sondage de 2021 mené auprès de personnes TGAS ont montré que celles qui avaient reçu des produits injectables pour le visage, sans chirurgie, faisaient état d’une meilleure estime d’elles-mêmes, d’une image corporelle plus positive, d’une meilleure adéquation de genre et d’une baisse de la discrimination anticipée de la part d’autrui, comparativement à celles qui n’en avaient pas reçu 9 . Une volumineuse étude transversale de 2021 a révélé que les femmes transgenres soumises à un traitement épilatoire d’affirmation de genre étaient en meilleure santé mentale que celles qui n’avaient pas reçu ce traitement 10 .…”
unclassified
“…The findings of a 2021 survey of TGD individuals showed that people who received nonsurgical facial injectables reported greater self-esteem, a more positive body image, greater gender congruence and less anticipated discrimination from others than people who did not. 9 A large 2021 cross-sectional study found that transgender women who received gender-affirming hair removal had better mental health status than those who did not. 10 Public health care payers may argue that appearance-enhancing procedures should be covered privately.…”
mentioning
confidence: 99%